HUBUNGAN PEKERJAAN IBU, TINGKAT PENDIDIKAN, PENGETAHUAN TERHADAP PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS BURANGA KEC. KALEDUPA, KAB. WAKATOBI - Fadlan, Fadlan; Indah Sugandi (Medic Nutricia : Jurnal Ilmu Kesehatan, 2025)
Background: According to data from the 2021 Indonesian Nutritional Status Survey (SSGI), approximately 48% of infants under 6 months of age do not receive exclusive breastfeeding. Nationally, the coverage of 6-month-old infants receiving exclusive breastfeeding in 2023 was 63.9%. This achievement has exceeded the 2023 program target of 50%. Objective: This study aimed to determine the relationship between maternal occupation, education level, and knowledge with exclusive breastfeeding in the Buranga Community Health Center (Puskesmas) work area, Kaledupa District, Wakatobi Regency. Method: This study used a quantitative method with an observational design. This method aims to explore how and why a health phenomenon occurs, as well as analyze the dynamics of the relationship between the phenomenon or risk factors and the effect factors. Results: This study aimed to determine the distribution of maternal occupation, education level, and knowledge with exclusive breastfeeding in the Buranga Community Health Center (Puskesmas) work area, Kaledupa District, Wakatobi Regency. Wakatobi in 2025. It is known that of the 35 mothers, more than half (51.4%) are working mothers, some (57.1%) have low education, the majority (54.3%) have poor knowledge, and more than half of the mothers (54.3%) do not provide exclusive breastfeeding. Conclusion: There is a relationship between maternal employment and exclusive breastfeeding with a p-value of 0.000 <0.05, there is a relationship between education level and exclusive breastfeeding with a p-value of 0.005 <0.05, there is a relationship between knowledge and exclusive breastfeeding with a p-value of 0.000 <0.05.